Perbandingan Interval Training dan Circuit Training terhadap Peningkatan Daya Tahan Anaerobik SSB Putra Mororejo U-16 - Rocky Alexander Ramadhan; Muh Isna Nurdin Wibisana; Pandu Kresnapati (Journal of Physical Activity and Sports (JPAS), 2021)
The purpose of this study was to determine the effect of interval training and circuit training on the anaerobic endurance of soccer players on the SSB Putra Mororejo U-16 team. The method in this research is an experimental research design with a Quasi Experiment Design with a pretest-posttest control group design. The instrument used to measure anaerobic endurance is the Running-based Anaerobic Sprint Test (RAST). The sample of this study was 20 players of SSB Putra Mororejo who were divided into two groups, namely the interval training group and the circuit training group. The results of the paired sample t-test concluded that there was an effect of treatment interval training and circuit training on anaerobic endurance. In the independent sample t test, interval training was more effective in increasing anaerobic endurance than circuit training. This is evidenced by the data obtained that the increase in interval training has a percentage increase of 40.96% and circuit training has an increased percentage of 24.96%. Based on the results of the study, it can be concluded that interval training is more effective than circuit training in an effort to increase anaerobic endurance. Keywords: interval training, circuit training, anaerobic endurance. Abstrak Tujuan penelitian ini adalah untuk mengetahui pengaruh interval training dan circuit training terhadap daya tahan anaerobik pemain sepak bola pada tim SSB Putra Mororejo U-16. Metode dalam penelitian ini adalah eksperimen dengan desain penelitian Quasi Eksperimen Design dengan pretest-posttest control group design. Instrument yang digunakan untuk mengukur daya tahan anaerobik adalah Running-based Anaerobic Sprint Test (RAST). Sampel dari penelitian ini adalah 20 pemain SSB Putra Mororejo yang dibagi dalam dua kelompok yaitu kelompok interval training dan circuit training. Hasil uji paired sample t-test disimpulkan bahwa ada pengaruh treatment interval training dan circuit training terhadap daya tahan anaerobik. Pada uji independent sample t test, interval training lebih efektif dalam upaya peningkatan daya tahan anaerobik daripada circuit training. Hal itu dibuktikan dengan diperolehnya data peningkatan interval training memiliki presentase peningkatan sebesar 40,96% dan circuit training memiliki peningkatan presentase sebesar 24,96%. Berdasarkan hasil penelitian dapat disimpulkan bahwa interval training lebih efektif dibandingkan circuit training dalam upaya peningkatan daya tahan anaerobik.